High‐altitude adaptations mitigate risk for hypertension and diabetes‐associated anemia. Issue 2 (23rd April 2020) - Wander, Katherine; Su, Mingjie; Mattison, Peter M.; Sum, Chun‐Yi; Witt, Christopher C.; Shenk, Mary K.; Blumenfield, Tami; Li, Hui; Mattison, Siobhán M.
Abstract: Background: Human populations native to high altitude exhibit numerous genetic adaptations to hypobaric hypoxia. Among Tibetan plateau peoples, these include increased vasodilation and uncoupling of erythropoiesis from hypoxia. Objective/Methods: We tested the hypothesis that these high‐altitude adaptations reduce risk for hypertension and diabetes‐associated anemia among the Mosuo, a Tibetan‐descended population in the mountains of Southwest China that is experiencing rapid economic change and increased chronic disease risk. Results: Hypertension was substantially less common among Mosuo than low‐altitude Han populations, and models fit to the Han predicted higher probability of hypertension than models fit to the Mosuo. Diabetes was positively associated with anemia among the Han, but not the Mosuo. Conclusion: The Mosuo have lower risk for hypertension and diabetes‐associated anemia than the Han, supporting the hypothesis that high‐altitude adaptations affecting blood and circulation intersect with chronic disease processes to lower risk for these outcomes. As chronic diseases continue to grow as global health concerns, it is important to investigate how they may be affected by local genetic adaptations.